KAP Study of Seven Factors of Enlightenment - Thein, Myo (Prajñā Journal of Buddhist Studies, 2026)
This paper “KAP Study of Seven Factors of Enlightenment” is a research paper which consists of Buddhist dhamma - Bojjhańgas, concepts of Buddhist Philosophy, benefits of chanting these factors to relieve illness and the ways of practicing meditation by focusing these factors in mind. It includes a field study to detect the knowledge, attitude and practice of students of Buddhist Nikaya Studies and meditators of Ledi Buddhist meditation center. This paper also describes how to prepare the mind for meditation in practicing four types of satipaṭṭhānaṁ technique. However, this paper will help people to gain some knowledge on seven factors that will guide yogi to attain enlightenment.